Festival Anak Sholeh Sebagai Sarana Penanaman Nilai Regelius Dan Rasa Percaya Diri Anak-Anak Di Desa Jembak Juara Muara Tembesi Batang Hari - Mahdayeni; Zilawati; Nofriza aulia; Lili trisnaliati; Uci Mayori; Nia Riyati (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
The Saleh Children's Festival is one of the joint work programs organized by IAI NUSANTARA BATANGHARI KKN Students in Jebak Village. The definition of a pious child is a person who does good or can be interpreted as increasing faith and obedience in worshiping Allah SWT. The aim of holding this pious children's festival program is 1. to increase enthusiasm for learning about Islam, 2. to develop interest and talent in the field of religion and, 3. to increase the self-confidence of the children of Jebak village. In implementing the pious children festival program there are 4 competition categories, namely: Adhan competition, Short Letter Memorization competition, Tartil and Calligraphy Coloring for preschool children. The method of implementing activities is by analyzing the needs of elementary school age children, planning, implementing, evaluating and following up the activities that have been taught. The results of this pious children's festival program are that the children of Jebak Village are more enthusiastic in studying Islam, then the children of Jebak Hamlet are also more courageous to show their talents and their self-confidence increases after participating in the pious children's festival program. This is proven by several boys from Jebak Village who initially did not dare to do the call to prayer after the pious children's festival was held, becoming brave enough to do the call to prayer.